Adaptive learning to enhance students understanding in learning technology experience - Alrashedi, Nashmi (Technium Social Sciences Journal, 2020)
One of the difficult problems at the present stage of development of education is the creation of conditions for the full realization of the student's personality. As one of the ways to solve it, the creation of an adaptive educational process is considered, which is built taking into account the capabilities of students, focuses on meeting their diverse needs and interests, provides conditions for their life self-determination and self-realization, creates a favorable psychological climate for the pedagogical interaction of all subjects of the educational environment. Thus, the paper is based upon adaptive education technologies used to reflect the cooperation of subjects, dialogue, the solution of personally significant tasks, free testing of experience.